PERSEKUTUAN KOMANDITER (COMMANDITAIRE VENNOOTSCHAP ATAU CV) SEBAGAI BADAN USAHA DALAM KAJIAN HUKUM PERUSAHAAN - Rosida Diani; Mahendra Kusuma (Justici, 2020)
Abstract Limited partnership or better known as CV is one type of business entity in the community. Specific regulations governing the limited partnership have not yet existed. The arrangement of this limited partnership in the KUHD is only in three articles, namely articles 19, 20 and 21. It is in the midst of regulating the alliance of firms. The problem to be elaborated in this research is whether the establishment of a limited partnership must be with an authentic deed? And what are the characteristics of a limited partnership so that it is a business entity not a legal entity. This research method uses normative juridical research or doctrinal law research. From the results of the study it was found that the establishment of a limited partnership may not be in the form of an authentic deed, this can be interpreted from the end of article 22 of the Criminal Code. Even if it refers to article 1618 of the Civil Code, article 16 and article 19 of the KUHD, the Alliance of Commanders can be established verbally. The limited partnership only has an element of separate wealth, has a specific purpose, and there are several people as administrators. There is no element of government approval on the deed of establishment. So without that endorsement, the limited partnership can not be categorized as a legal entity.